Analysis of the influence of exogenous factors on indoor air quality in residential buildings - Nibagwire, Deborah; Ana, Godson R. E. E.; Kalisa, Egide; Twagirayezu, Gratien; Safari Kagabo, Abdou; Nsengiyumva, Jacques (Frontiers in Built Environment, 2025)
Indoor air pollution presents a significant global health risk, yet the influence of outdoor air pollution and meteorological factors on indoor air quality is not well understood. This study investigates these impacts in 88 naturally ventilated households across urban, suburban, and industrial areas, with no indoor smoking or cooking. Air quality measurements were continuously recorded for 24 h a day over six consecutive days during the wet season. The findings reveal that the outdoor PM2.5 levels consistently exceeded indoor levels, with weekday concentrations higher than on weekends. Specifically, urban PM2.5 levels averaged 34.8 μg/m³ outdoors and 31 μg/m³ indoors on weekdays, compared to 33.1 μg/m³ outdoors and 31.5 μg/m³ indoors on weekends. Indoor CO2 levels were notably higher, peaking at 525.7 ppm in urban areas on weekdays and 576.9 ppm on weekends, driven by increased occupancy and poor ventilation, particularly in suburban areas (880.4 ppm on weekdays and 807.5 ppm on weekends). The average indoor/outdoor (I/O) ratio for PM2.5 was 0.94, indicating that indoor concentrations are about 94% of outdoor levels, signifying significant infiltration of outdoor pollution. In contrast, the I/O ratio for CO2 was 1.47, suggesting indoor levels were 47% higher due to limited ventilation and indoor sources. This study concludes that outdoor air pollution and meteorological factors significantly affect indoor air quality in Kigali, Rwanda, highlighting the need for effective management of both outdoor pollution sources and indoor conditions.